Pengaruh musim terhadap kelimpahan kumbang moncong (Coleoptera: Curculionidae) pada tipe penggunaan lahan berbeda di lanskap Hutan Harapan dan Taman Nasional Bukit Duabelas, Jambi - Fatimah Siddikah; Rizky Nazarreta; Damayanti Buchori (Perhimpunan Entomologi Indonesia, 2020)
Land-use change from forest to plantation can cause the loss of various types of insect diversity group, one of which is the beetle group. Curculionids or weevils is one of the largest families in the Order Coleoptera due to its adaptability in almost all habitats in nature. This research is aimed to study the effect of seasonality on species richness and the abundance of weevils in oil palm and rubber plantation in Hutan Harapan and Bukit Duabelas National Park, Jambi. Sample was collected in the dry season and rainy season 2013–2014 by fogging method using pyrethroid knockdown insecticides. In each land use, 4 observation plots were erected with selected 3 points as a subplots, so there are 16 plots or 48 subplots in total. The results showed that 1.761 individuals of weevils from 9 subfamilies and 45 morphospecies. Based on analysis, seasonal difference did not affect species richness and abundance of weevils, while land-use types affect abundance of weevils. Analysis of similarity using Bray-Curtis Index showed 4% of similarity in two land-use types, and 46% of similarity between two seasons. The diversity index in oil palm plantation were lower than rubber plantation. The most dominant species that can be found in both land-use types is Elaeidobius kamerunicus Faust., while Rhynchophorus sp.01 is only found in oil palm plantation, and Curculio sp.04 is only found in rubber plantation.